Enhancement of soil microbial community stability by earthworms and collembolans in soil from abandoned coal mine lands - Jia, Junli; Chen, Linghui; Liu, Qian; Wang, Kai; Zhao, Kang; Ren, Xiaoyu; Gao, Xue; Ani, Jianmei (Frontiers in Microbiology, 2026)
Soil fauna play a critical role in the restoration of abandoned mining areas, uniquely contributing to soil formation, development, and the rehabilitation of degraded soils. This role is intricately linked with miwcrobial activity. Previous research has mainly concentrated on the direct effects of soil fauna on the physicochemical properties of soils in abandoned sites, often overlooking their indirect impacts on soil ecological functions via changes in soil microbial communities. This study undertakes a microcosm experiment by introducing soil fauna into the soil from coal mining abandoned lands to explore shifts in microbial communities. Results demonstrate that collembolan treatments significantly reduce fungi abundance, whereas earthworm treatments notably decrease the Shannon and Chao1 index for both bacterial and fungi communities. Soil fauna treatments modify the structure and composition of microbial communities, with more distinct differences in fungi community structures. Additionally, various soil fauna treatments markedly change microbial interactions; earthworm treatments impact microbial communities more than collembolan treatments, and combined treatments (EC) are more effective in enhancing microbial community stability compared to individual treatments (C, E). Network analysis has identified key microbial taxa that are positively correlated with soil fauna abundance, suggesting that future management strategies could manipulate key microbial taxa through soil fauna to enhance the restoration of soil ecological functions. These findings offer a detailed understanding of the dynamics of microbial communities under biotic interactions, essential for the ecological restoration of soils in abandoned mining areas.